Site-Directed Mutagenesis of Surface-Exposed Lysine Residues Leads to Improved Transduction by AAV2, But Not AAV8, Vectors in Murine Hepatocytes In Vivo - Li, Baozheng (Hum Gene Ther Methods, 2015)
The ubiquitin–proteasome pathway plays a critical role in the intracellular trafficking of recombinant adeno-associated virus 2 (AAV2) vectors, which negatively impacts the transduction efficiency of these vectors. Because ubiquitination occurs on lysine (K) residues, we performed site-directed mutagenesis where we replaced each of 10 surface-exposed K residues (K258, K490, K507, K527, K532, K544, K549, K556, K665, and K706) with glutamic acid (E) because of similarity of size and lack of recognition by modifying enzymes. The transduction efficiency of K490E, K544E, K549E, and K556E scAAV2 vectors increased in HeLa cells in vitro up to 5-fold compared with wild-type (WT) AAV2 vectors, with the K556E mutant being the most efficient. Intravenous delivery of WT and K-mutant ssAAV2 vectors further corroborated these results in murine hepatocytes in vivo. Because AAV8 vectors transduce murine hepatocytes exceedingly well, and because some of the surface-exposed K residues are conserved between these serotypes, we generated and tested two single mutants (K547E and K569E), and one double-mutant (K547 + 569E) AAV8 vector. However, no significant increase in the transduction efficiency of any of these mutant AAV8 vectors was observed in murine hepatocytes in vivo. These studies suggest that although targeting the surface-exposed K residues is yet another strategy to improve the transduction efficiency of AAV vectors, phenotypic outcome is serotype specific.